Nurse Staffing and Workload Drivers in Small Rural Hospitals: An imperative for Evidence - Diane E Twigg; Jennifer H Cramer; Judith D Pugh (Rural Nurse Organization; Binghamton University, 2016)
Purpose: The aim of this study was to explore staffing issues and the workload drivers influencing nursing activities in designated small rural hospitals of Western Australia. A problem for small rural hospitals is an imbalance between nurse staffing resources and work activity. Sample: A purposive sample of 17 nurse leaders employed at designated small rural hospitals in Western Australia. Method: A qualitative research design was used. Data were collected by focus group and semi-structured interviews and review of Western Australian Country Health Service records. Thematic analysis was used to interpret data. Findings: A minimum nurse staffing model is in use. Staff workload is generated from multiple activities involving 24-hour emergency services, inpatient care, and other duties associated with a lack of clinical and administrative services. These factors together impact on nursing staff resources and the skill mix required to ensure the safety and quality of patient care. Conclusion:  Nurse staffing for small rural hospitals needs site-specific recording techniques for workload measurement, staff utilisation and patient outcomes. It is imperative that evidence guide nurse staffing decisions and that the workload driving nursing activity is reviewed.  Keywords: rural health nursing; nursing staff; skill mix; workload; workload measurement; hospitals, rural; rural health services DOI:  http://dx.doi.org/10.14574/ojrnhc.v16i1.370